Farmers’ Satisfaction with Agricultural Extension: A Service Quality-based Assessment - Shaba, Sharjana Akter; Alam, Md Mahbubul (Indian Journal of Extension Education, 2024)
With an aim to contribute to the methodology in Agricultural Extension research and draw extension professionals’ attention to evaluating farmers’ satisfaction with extension service delivery, this research presents a comparative evaluation of the traditional research approach, which treats farmers’ selected socioeconomic characteristics as the predictor variables against SERVQUAL five-dimensions (i.e., tangibility, reliability, assurance, responsiveness, and empathy). The study was carried out from 2022-2023 and data used in this research were collected from August 01 to August 15, 2022. Stratified random sampling was used to select 120 farmers from two unions of the Savarupazila (i.e., sub district) of Dhaka district, Bangladesh, and analyzed using hierarchical regression analysis. Results revealed that without using SERVQUAL dimensions, farmers’ socioeconomic characteristics explained 30.9 per cent of the variance of their satisfaction when SERVQUAL dimensions were not used. However, this percentage increased to 61.8 per cent upon adding SERVQUAL dimensions to the model. Therefore, the findings provide a novel dimension for further research on farmers’ satisfaction with agricultural extension and evaluate similar agriculture-based rural development programs.
Keywords: Service quality; Farmer satisfaction; SERVQUAL model; Agricultural extension